A triz-directed approach in proposing device-oriented ideas that cultivate water-drinking habits among children. Issue 1 (1st January 2021) - Tan, Robin Edmund Jin Hong; Ng, Poh Kiat; Tan, Dominic Wen How; Lim, Way Soong
Abstract: This study aims to investigate problems concerning water-drinking habits among children, ongoing efforts to resolve these problems, limitations in these ongoing efforts and recommended ideas to overcome these limitations. The TRIZ approach was used primarily to identify the root causes of the main problem and establish technical contradictions in order to steer the researchers to specific solution models. The solution models generated from the 40 inventive principles of TRIZ were used to recommend ideas that could potentially resolve the technical contradictions. The recommended ideas were then substantiated with existing research, concepts or analogies in order to authenticate their practicalities with regard to the study's aim. The inventive principles extracted include the universality, preliminary action and segmentation principles. The principles used allowed the proposal of inventive design recommendations at the end of the study. For instance, based on the segmentation principle, the idea to improve water-drinking habits among children can be in the form of a water bottle that is compartmentalised into two parts; the top part being the containment unit for the water and the bottom part being the storage section for a reward beverage (perhaps a sweet drink such as orange juice or syrup). The compartmentalised water bottle idea would entice children to completely consume the water in the bottle before accessing the reward beverage. Although further research and verifications are still required, the proposed ideas can serve as precursory recommendations for researchers and designers in their pursuits to improve the water-drinking habits among children in future.